Fast exact string matching algorithms - Lecroq, Thierry (Information processing letters, 2007)
String matching is the problem of finding all the occurrences of a pattern in a text. We propose a very fast new family of string matching algorithms based on hashing q-grams. The new algorithms are the fastest on many cases, in particular, on small size alphabets.